PERAN GURU PENDIDIKAN PANCASILA PADA LOMBA KEBERSIHAN KELAS DALAM MENINGKATKAN KARAKTER PEDULI LINGKUNGAN DI SMP NEGERI 2 GELUMBANG - Puspita Sari, Reni; Dianti, Puspa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to determine the role Pancasila Education teachers in classroom cleanliness competition in enhancing students’ environmental care character at SMP Negeri 2 Gelumbang. This research employs a descriptive qualitative approach using a study method. The informants were selected through purposive sampling, involving five participants. Data collection techniques included interviews, observations, and documentation. Data validity was ensured through credibility, transferability, dependability, and corfirmability tests. In essence, the role of Pancasila Education teachers plays a crucial role in raising student’s awareness of enviromental cleanliness. Good character in students is typically forestered through education, learning, anf and facilities built on sound morals. A well-developed enviromental stewardship will undoubtedly have a positive impact in the future, preventing a dirty and uncomfortable enviroment, especially in the school enviroment. Therefore, The role of Pancasila Education teacher is crucial in instilling an environmentally conscious attitude in students in the classroom and fostering a sense of environmental cleanliness. One way schools foster this environmental stewardship is through classroom cleanliness competitions. These competitions are held regularly once a week. The purpose of the activities is to foster student’s awareness of the school environmentally by maintaining and caring for the enviroment to keep it clean and tidy. This allows the teaching and learning process between teachers and students to be more comfortable and conducive.